High-temperature-resistant metallurgical vehicle-mounted flexible cable and preparation method thereof

By using composite cable design of polyimide, polyphenylene sulfide, polybenzimidazole and polyether ether ketone/nano silica composite materials, the lack of performance of traditional metallurgical vehicle-mounted cables in high temperature and complex environments is solved. It has achieved improvements in high temperature resistance, flexibility and toughness, reducing production difficulty and cost.

CN119480242AInactive Publication Date: 2025-02-18GUANG DONG LI GUANG DIAN QI SHI YE YOU XIAN GONG SI

Patent Information

Application Number
CN202411636520.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional metallurgical vehicle-mounted cables show insufficient high-temperature resistance, low tensile strength and wear resistance, poor corrosion resistance and poor structure in high temperature, high vibration and strong corrosion resistance, which cannot meet the signal transmission of modern metallurgical equipment. High precision, stability and real-time requirements.

Method used

Using integrated composite materials as sheath and internal filler, the material consists of polyimide, polyphenylene sulfide, polybenzimidazole and polyether etherketone/nano-silica composites, through the combination of these materials and nano The surface treatment of silica improves the material's high temperature resistance, flexibility and toughness.

Benefits of technology

It achieves the improvement of the high temperature resistance of the cable, enhances flexibility and toughness, reduces production difficulty and cost, simplifies the production process, and improves the overall performance and adaptability of the cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005137271390000091
    Figure BDA0005137271390000091
  • Figure BDA0005137271390000101
    Figure BDA0005137271390000101
Patent Text Reader

Abstract

The invention belongs to the technical field of cables, and particularly relates to a high-temperature-resistant metallurgical vehicle-mounted flexible cable and a preparation method thereof. According to the high-temperature-resistant cable material, polyimide, polyphenylene sulfide and polybenzimidazole are matched, so that the high-temperature-resistant cable material is endowed with extremely high high temperature resistance, can resist the high temperature of 300 DEG C, and is extremely suitable for cable materials for metallurgy. Then, the flexibility of the material is improved by adding a flexible polyether-ether-ketone / nano silicon dioxide compound, and the surface of nano silicon dioxide is treated, so that the loading rate of polyether-ether-ketone can be increased, the phase separation phenomenon of polyether-ether-ketone in a blend is prevented, and uniform dispersion is promoted. And finally, the prepared high-temperature-resistant metallurgical vehicle-mounted flexible cable material is used as a filler and a sheath of the cable material, so that the cable structure is reduced, the production difficulty of the cable is reduced, the production process is simplified, and the material and process requirements are reduced, thereby achieving the purposes of reducing the cost and improving the production efficiency to a certain extent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cables, and in particular relates to a high-temperature resistant metallurgical vehicle-mounted flexible cable and a preparation method thereof. Background Art

[0002] In the metallurgical industry, on-board cables are important components for connecting various types of equipment, and their performance directly affects the stable operation of the equipment. Metallurgical on-board cables need to work in extreme environments, such as high temperature, high humidity, high vibration and strong corrosive conditions, which puts extremely high demands on the structure, materials and manufacturing process of the cables. Traditional metallurgical on-board cables usually use copper conductors and ordinary rubber as insulation and sheath materials. However, with the advancement of metallurgical industry technology and higher requirements for production efficiency and reliability, traditional cables have gradually exposed some shortcomings.

[0003] The disadvantages of traditional technology are:

[0004] Insufficient high temperature resistance: The insulation and sheath materials of traditional cables are mainly made of ordinary rubber, which is prone to aging and cracking in high temperature environments, causing the insulation performance of the cable to decline rapidly, increasing the risk of short circuits and safety accidents. In addition, oxidation and thermal decomposition reactions in high temperature environments will also accelerate the degradation of materials and shorten the service life of the cable.

[0005] Low tensile strength and wear resistance: Metallurgical equipment usually needs to be moved frequently, and the cable is subjected to large tension and wear. Ordinary rubber materials have poor tensile strength and wear resistance, and are prone to breakage due to repeated bending and stretching. At the same time, mechanical impact and wear may also cause damage to the sheath layer, exposing the internal conductor, further reducing the reliability of the cable.

[0006] Poor corrosion resistance: In metallurgical environments, cables are often exposed to corrosive gases and liquids. Traditional cable materials have poor resistance to acid and alkali corrosion and are easily affected by chemical corrosion, resulting in degradation of cable performance and even conductive failures.

[0007] Uncompact structure: The structural design of traditional cables is usually relatively simple, and often cannot strike a balance between electrical performance and mechanical strength. Especially in complex environments, cables with uncompact structures are prone to internal conductor displacement, short circuits, or electrical performance degradation.

[0008] Poor signal transmission stability: Traditional cables are mainly used for power transmission and lack consideration for signal control. With the increasing demand for intelligence and automation, traditional cables cannot effectively meet the requirements of modern metallurgical equipment for high precision, stability and real-time signal transmission.

[0009] In view of the above disadvantages of traditional metallurgical vehicle cables, the existing technology has made a number of improvements to improve the overall performance and adaptability of the cables. These improvements are mainly reflected in material selection, structural design and manufacturing process.

[0010] Among them, CN 110675984 B discloses a high-temperature metallurgical vehicle-mounted flexible cable and its production process. It adopts a composite structure, separates the control line core and the power line core, and uses multi-mode optical fiber and Mylar tape to wrap to form a compact cable structure. This design ensures a compact cable structure, stable signal transmission, a small bending radius, strong bending resistance, and a long service life.

[0011] In the conductor design, multiple copper wires are twisted in a specific structure by twisting in the same direction and layered, which not only meets the electrical performance requirements (such as 20°C DC resistance) but also reduces the outer diameter of the conductor. This design enhances the flexibility of the cable, reduces the outer diameter of the cable, and makes it easier to transport and install.

[0012] Integrating multimode optical fiber in the gap of the control core enables the cable to monitor the operating temperature and current carrying capacity in real time during operation, and quickly feed back the information to the control system, enhancing the cable's monitoring and control capabilities.

[0013] The insulation layer and sheath materials are made of a new flame-retardant and environmentally friendly silicone mixture that meets the EN50382 standard. This material has excellent tensile, wear-resistant, bending and high-temperature resistance, thereby improving the overall durability of the cable.

[0014] A reinforcement layer made of aramid yarn is placed outside the inner lining layer to improve the tensile strength and durability of the cable. This design also ensures the stability of the cable under high stress conditions.

[0015] The insulation layer and jacket are produced through a continuous steam vulcanization process, which improves the elasticity and tensile properties of the material, thereby enhancing the durability of the cable.

[0016] Although this design is excellent in many ways, it has some potential drawbacks:

[0017] The first is structural complexity: the cable's multi-layer composite structure and the use of multiple materials may lead to complex production processes, increasing manufacturing costs and production difficulty.

[0018] Secondly, size control is difficult: although the compression of the outer diameter is emphasized in the cable design, the multi-layer structure and the thickness control of various materials need to be very precise. A slight deviation may cause the overall size of the cable to exceed expectations.

[0019] Finally, it is difficult to strike a balance between high temperature resistance and flexibility: although silicone materials have good high temperature resistance, their flexibility may be affected under extremely high temperatures, and this balance needs to be further verified in practical applications.

[0020] These defects not only greatly increase the cost of cable production, but also greatly increase the difficulty of cable production. Therefore, a new design idea is needed to reduce the difficulty of cable production, simplify the production process, reduce material and process requirements, thereby reducing costs and improving production efficiency to a certain extent. Summary of the invention

[0021] In view of the shortcomings of the prior art, the present invention provides a high-temperature resistant metallurgical vehicle-mounted flexible cable and a preparation method. The present invention considers using an integrated composite material to replace the multi-layer structure, and develops a flexible material with insulation, shielding, wear resistance and tensile resistance to replace the sheath and internal filler, thereby reducing the design requirements of the internal complex structure, reducing the difficulty of cable production, simplifying the production process, and reducing material and process requirements, thereby reducing costs and improving production efficiency to a certain extent.

[0022] The present invention provides a high-temperature resistant metallurgical vehicle-mounted flexible cable, comprising three power lines, three control lines, and an integrally formed high-temperature resistant sheath, wherein the three power lines and the three control lines are located inside the integrally formed high-temperature resistant sheath.

[0023] The three power cores are arranged at 120° intervals in pairs, the three control cores are respectively arranged between two of the power cores, and adjacent power cores are tangent to adjacent control cores; the cabled filled insulation core is tangent to the three power cores.

[0024] The material of the integrally formed high temperature resistant sheath is a flexible cable material for high temperature resistant metallurgy vehicles.

[0025] The high temperature resistant metallurgical vehicle-mounted flexible cable material is composed of the following raw materials: polyimide, polyphenylene sulfide, polybenzimidazole, polyetheretherketone / nano silicon dioxide composite, and anti-aging agent.

[0026] Preferably, the high temperature resistant metallurgical vehicle-mounted flexible cable material is composed of the following raw materials, measured by mass: 50-80 parts of polyimide, 1-5 parts of polyphenylene sulfide, 3-8 parts of polybenzimidazole, 10-20 parts of polyetheretherketone / nanosilica composite, and 1-2 parts of anti-aging agent.

[0027] Further preferably, the high temperature resistant metallurgical vehicle-mounted flexible cable material is composed of the following raw materials, by mass: 50-60 parts of polyimide, 1-3 parts of polyphenylene sulfide, 3-5 parts of polybenzimidazole, 10-12 parts of polyetheretherketone / nanosilica composite, and 1-2 parts of anti-aging agent.

[0028] The anti-aging agent is at least one of styrene-butadiene copolymer and polyether polyol.

[0029] The preparation method of the polyetheretherketone / nano-silicon dioxide composite comprises the following steps:

[0030] S1: mixing a silane coupling agent and ethanol in a volume ratio of 1:(5-10), stirring at room temperature for 10-20 minutes to obtain an ethanol solution of the silane coupling agent, and then mixing nano-silica and the ethanol solution of the silane coupling agent in a mass ratio of 1:(10-20), stirring at room temperature for 1-2 hours, centrifuging, washing, and drying to obtain nano-silica modified with a silane coupling agent;

[0031] S2: dissolving polyetheretherketone in N-methylpyrrolidone to obtain a 10-20wt% polyetheretherketone solution, adding the silane coupling agent-modified nano-silica obtained in step S1 to the above 10-20wt% polyetheretherketone solution, so that the mass ratio of polyetheretherketone to the silane coupling agent-modified nano-silica is (1-2):1, stirring at room temperature for 1-2h, filtering, washing, and drying to obtain the polyetheretherketone / nano-silica composite.

[0032] The silane coupling agent is at least one of γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and γ-aminopropyltrimethoxysilane; preferably, the silane coupling agent is γ-aminopropyltriethoxysilane.

[0033] The present invention also provides a method for preparing a high-temperature resistant metallurgical vehicle-mounted flexible cable material, comprising the following steps: mixing polyimide, polyphenylene sulfide, polybenzimidazole, polyetheretherketone / nano-silica composite, and anti-aging agent in parts by mass, placing in an internal mixer and internally kneading for 20-30 minutes at a mixing temperature of 360-380°C, and cooling to room temperature to obtain the high-temperature resistant metallurgical vehicle-mounted flexible cable material.

[0034] The present invention also provides a method for preparing a high-temperature metallurgical vehicle-mounted flexible cable, comprising the following steps: determining the structure of three power lines and three control lines, then softening the high-temperature metallurgical vehicle-mounted flexible cable material, directly injection molding, and cooling to obtain the high-temperature metallurgical vehicle-mounted flexible cable.

[0035] In the present invention, firstly, the combination of polyimide, polyphenylene sulfide and polybenzimidazole gives the material extremely strong high temperature resistance, can withstand 300°C high temperature, and is extremely suitable for metallurgical cable materials. The polyimide molecular structure contains rigid aromatic rings and imide groups, which give it extremely high thermal stability and mechanical strength. However, this highly rigid structure also leads to limited flexibility of the material itself, and it is easy to brittle fracture when subjected to force. Secondly, polyphenylene sulfide is a typical liquid crystal polymer with a linear rigid molecular chain structure, and the aromatic ring in the molecule further enhances the rigidity of the material. Next, the molecular structure of polybenzimidazole contains benzimidazole rings, which makes polybenzimidazole have extremely high heat resistance and mechanical strength, especially in high temperature environment. Stability can still be maintained. However, polybenzimidazole has a large rigidity. Although it has excellent tensile strength, it also has the problem of insufficient flexibility and is prone to brittle fracture under high stress. The common characteristics of these three materials are that they have the characteristics of high rigidity, high strength and good heat resistance, but relatively poor flexibility. When the material combination only contains polyimide, polyphenylene sulfide, and polybenzimidazole, it is easy to form a brittle material, especially when the stress is concentrated or the force is uneven, the material is more likely to break or break. Therefore, it is necessary to add a flexible material to make up for this defect.

[0036] The present invention improves the flexibility of the material by adding a flexible polyetheretherketone / nano-silicon dioxide composite. Polyetheretherketone, as a semi-crystalline thermoplastic polymer, has certain flexibility and high elongation at break. Its molecular structure contains flexible ether bonds and ketone groups, which can introduce certain flexibility into the material structure and alleviate the brittleness problem caused by rigid polymers. In the composite material, the role of polyetheretherketone is to provide flexibility and toughness, and compensate for the rigidity brought by polyimide, polyphenylene sulfide, and polybenzimidazole. When polyetheretherketone is missing, the overall flexibility of the material will be significantly reduced, and brittle fracture will easily occur under stretching, bending or impact.

[0037] After surface treatment, nano-silica can enhance the compatibility between polymers and improve the interfacial bonding force, thereby improving the toughness and strength of the composite material. In addition, nano-silica can form a uniform stress dispersion in the polymer matrix through good dispersibility, which helps to absorb externally applied energy and reduce the occurrence of brittle fracture. The lack of nano-silica will lead to poor compatibility between materials and easy formation of phase separation structure, which will further reduce the toughness and overall mechanical properties of the composite material.

[0038] If the flexibility of polyetheretherketone in the material is not reflected, it means that the material lacks sufficient energy absorption and deformation ability under high stress. The absence of nano-silicon dioxide not only reduces the interfacial compatibility of the composite material, but also loses the stress dispersion effect, which makes the material more prone to local stress concentration under the action of external force, thereby leading to fracture.

[0039] In addition, polyetheretherketone has poor compatibility with other materials, and nano-silicon dioxide also plays a role in improving the compatibility of polyetheretherketone with polyimide, polyphenylene sulfide, and polybenzimidazole. By treating the surface of nano-silicon dioxide, the loading rate of polyetheretherketone can be increased, the phase separation of polyetheretherketone in the blend can be prevented, and uniform dispersion can be promoted.

[0040] Beneficial effects of the present invention:

[0041] The present invention endows the material with extremely strong high temperature resistance by combining polyimide, polyphenylene sulfide and polybenzimidazole, and can withstand a high temperature of 300° C., making it extremely suitable as a cable material for metallurgy.

[0042] Furthermore, the present invention improves the flexibility of the material by adding a flexible polyetheretherketone / nano-silicon dioxide composite, and by treating the surface of nano-silicon dioxide, the loading rate of polyetheretherketone can be increased, the phase separation of polyetheretherketone in the blend can be prevented, and uniform dispersion can be promoted.

[0043] Finally, the present invention uses the prepared high-temperature resistant metallurgical vehicle-mounted flexible cable material as the filler and sheath of the cable material, reduces the cable structure, reduces the difficulty of cable production, simplifies the production process, reduces material and process requirements, thereby reducing costs and improving production efficiency to a certain extent. DETAILED DESCRIPTION

[0044] Polyimide, CAS: 62929-02-6, Part No.: WD0284, Hubei Wonder Chemical Co., Ltd.

[0045] Polyphenylene sulfide, CAS: 25212-74-2, Part No.: KA672664, Shanghai Jieshikai Biotechnology Co., Ltd.

[0046] Polybenzimidazole, CAS: 25928-81-8, Part No.: M64537, Shanghai Myril Biochemical Technology Co., Ltd.

[0047] Polyetheretherketone, CAS: 29658-26-2, Part No.: HC7366, Tianmen Hengchang Chemical Co., Ltd.

[0048] Nano-silicon dioxide, particle size: 20 nm, Nanjing Baoket New Materials Co., Ltd.

[0049] Styrene-butadiene copolymer, product number: SCPP-80153, Shanghai Secor Biotechnology Co., Ltd.

[0050] Example 1

[0051] A high-temperature-resistant metallurgical vehicle-mounted flexible cable comprises three power lines, three control lines and an integrally formed high-temperature-resistant sheath, wherein the three power lines and the three control lines are located inside the integrally formed high-temperature-resistant sheath.

[0052] The three power cores are arranged at 120° intervals, and the three control cores are respectively arranged between the two power cores, and the adjacent power cores are tangent to the adjacent control cores; the cabled filling insulation core is tangent to the three power cores. The preparation method of the high temperature metallurgical vehicle-mounted flexible cable includes the following steps: determining the structure of the three power lines and the three control lines, then softening the high temperature metallurgical vehicle-mounted flexible cable material, directly injection molding, and cooling to obtain the high temperature metallurgical vehicle-mounted flexible cable.

[0053] The material of the one-piece high-temperature resistant sheath is a flexible cable material for high-temperature resistant metallurgical vehicles.

[0054] The high temperature resistant metallurgical vehicle-mounted flexible cable material is composed of the following raw materials, measured by mass: 55 parts of polyimide, 2 parts of polyphenylene sulfide, 4 parts of polybenzimidazole, 11 parts of polyetheretherketone / nano-silicon dioxide composite, and 1.5 parts of anti-aging agent.

[0055] The antioxidant is styrene-butadiene copolymer.

[0056] The preparation method of polyetheretherketone / nano-silicon dioxide composite comprises the following steps:

[0057] S1: mixing a silane coupling agent and ethanol in a volume ratio of 1:8, stirring at room temperature for 15 minutes to obtain an ethanol solution of the silane coupling agent, and then mixing nano-silica and the ethanol solution of the silane coupling agent in a mass ratio of 1:15, stirring at room temperature for 1.5 hours, centrifuging, washing, and drying to obtain nano-silica modified with a silane coupling agent;

[0058] S2: dissolving polyetheretherketone in N-methylpyrrolidone to obtain a 15wt% polyetheretherketone solution, adding the silane coupling agent-modified nano-silica obtained in step S1 to the above 15wt% polyetheretherketone solution, so that the mass ratio of polyetheretherketone to the silane coupling agent-modified nano-silica is 2:1, stirring at room temperature for 2h, filtering, washing and drying to obtain the polyetheretherketone / nano-silica composite.

[0059] The silane coupling agent is γ-aminopropyltriethoxysilane.

[0060] Example 2

[0061] The difference from Example 1 is that a high-temperature resistant metallurgical vehicle-mounted flexible cable material is composed of the following raw materials, by mass: 55 parts of polyimide, 2 parts of polyphenylene sulfide, 4 parts of polybenzimidazole, 11 parts of polyetheretherketone / nanosilica composite, and 1.5 parts of anti-aging agent.

[0062] The anti-aging agent is styrene-butadiene copolymer.

[0063] The preparation method of the polyetheretherketone / nano-silicon dioxide composite comprises the following steps:

[0064] Polyetheretherketone is dissolved in N-methylpyrrolidone to obtain a 15wt% polyetheretherketone solution, nano-silicon dioxide is added to the 15wt% polyetheretherketone solution so that the mass ratio of polyetheretherketone to nano-silicon dioxide is 2:1, the mixture is stirred at room temperature for 2h, filtered, washed and dried to obtain the polyetheretherketone / nano-silicon dioxide composite.

[0065] Example 3

[0066] The difference from Example 1 is that a high-temperature resistant metallurgical vehicle-mounted flexible cable material is composed of the following raw materials, by mass: 55 parts of polyimide, 2 parts of polyphenylene sulfide, 4 parts of polybenzimidazole, 11 parts of nano-silicon dioxide, and 1.5 parts of anti-aging agent.

[0067] The anti-aging agent is styrene-butadiene copolymer.

[0068] Example 4

[0069] The difference from Example 1 is that a high-temperature resistant metallurgical vehicle-mounted flexible cable material is composed of the following raw materials, by mass: 55 parts of polyimide, 2 parts of polyphenylene sulfide, 4 parts of polybenzimidazole, 11 parts of polyetheretherketone, and 1.5 parts of anti-aging agent.

[0070] The anti-aging agent is styrene-butadiene copolymer.

[0071] Example 5

[0072] The difference from Example 1 is that a high-temperature resistant metallurgical vehicle-mounted flexible cable material is composed of the following raw materials, calculated by mass: 55 parts of polyimide, 2 parts of polyphenylene sulfide, 4 parts of polybenzimidazole, and 1.5 parts of anti-aging agent.

[0073] The anti-aging agent is styrene-butadiene copolymer.

[0074] Comparative Example 1

[0075] The difference from Example 1 is that a high-temperature resistant metallurgical vehicle-mounted flexible cable material is composed of the following raw materials by mass: 55 parts of polyimide and 1.5 parts of anti-aging agent.

[0076] The anti-aging agent is styrene-butadiene copolymer.

[0077] Comparative Example 2

[0078] The difference from Example 1 is that a high-temperature resistant metallurgical vehicle-mounted flexible cable material is composed of the following raw materials, by mass: 55 parts of polyimide, 11 parts of polyetheretherketone / nano-silicon dioxide composite, and 1.5 parts of anti-aging agent.

[0079] The anti-aging agent is styrene-butadiene copolymer.

[0080] The preparation method of the polyetheretherketone / nano-silicon dioxide composite comprises the following steps:

[0081] S1: mixing a silane coupling agent and ethanol in a volume ratio of 1:8, stirring at room temperature for 15 minutes to obtain an ethanol solution of the silane coupling agent, and then mixing nano-silica and the ethanol solution of the silane coupling agent in a mass ratio of 1:15, stirring at room temperature for 1.5 hours, centrifuging, washing, and drying to obtain nano-silica modified with a silane coupling agent;

[0082] S2: dissolving polyetheretherketone in N-methylpyrrolidone to obtain a 15wt% polyetheretherketone solution, adding the silane coupling agent-modified nano-silica obtained in step S1 to the above 15wt% polyetheretherketone solution, so that the mass ratio of polyetheretherketone to the silane coupling agent-modified nano-silica is 2:1, stirring at room temperature for 2h, filtering, washing and drying to obtain the polyetheretherketone / nano-silica composite.

[0083] The silane coupling agent is γ-aminopropyltriethoxysilane.

[0084] Comparative Example 3

[0085] The difference from Example 1 is that a high-temperature resistant metallurgical vehicle-mounted flexible cable material is composed of the following raw materials, by mass: 55 parts of polyimide, 2 parts of polyphenylene sulfide, 11 parts of polyetheretherketone / nano-silica composite, and 1.5 parts of anti-aging agent.

[0086] The anti-aging agent is styrene-butadiene copolymer.

[0087] The preparation method of the polyetheretherketone / nano-silicon dioxide composite comprises the following steps:

[0088] S1: mixing a silane coupling agent and ethanol in a volume ratio of 1:8, stirring at room temperature for 15 minutes to obtain an ethanol solution of the silane coupling agent, and then mixing nano-silica and the ethanol solution of the silane coupling agent in a mass ratio of 1:15, stirring at room temperature for 1.5 hours, centrifuging, washing, and drying to obtain nano-silica modified with a silane coupling agent;

[0089] S2: dissolving polyetheretherketone in N-methylpyrrolidone to obtain a 15wt% polyetheretherketone solution, adding the silane coupling agent-modified nano-silica obtained in step S1 to the above 15wt% polyetheretherketone solution, so that the mass ratio of polyetheretherketone to the silane coupling agent-modified nano-silica is 2:1, stirring at room temperature for 2h, filtering, washing and drying to obtain the polyetheretherketone / nano-silica composite.

[0090] The silane coupling agent is γ-aminopropyltriethoxysilane.

[0091] Comparative Example 4

[0092] The difference from Example 1 is that a high-temperature resistant metallurgical vehicle-mounted flexible cable material is composed of the following raw materials, by mass: 55 parts of polyimide, 4 parts of polybenzimidazole, 11 parts of polyetheretherketone / nano-silicon dioxide composite, and 1.5 parts of anti-aging agent.

[0093] The anti-aging agent is styrene-butadiene copolymer.

[0094] The preparation method of the polyetheretherketone / nano-silicon dioxide composite comprises the following steps:

[0095] S1: mixing a silane coupling agent and ethanol in a volume ratio of 1:8, stirring at room temperature for 15 minutes to obtain an ethanol solution of the silane coupling agent, and then mixing nano-silica and the ethanol solution of the silane coupling agent in a mass ratio of 1:15, stirring at room temperature for 1.5 hours, centrifuging, washing, and drying to obtain nano-silica modified with a silane coupling agent;

[0096] S2: dissolving polyetheretherketone in N-methylpyrrolidone to obtain a 15wt% polyetheretherketone solution, adding the silane coupling agent-modified nano-silica obtained in step S1 to the above 15wt% polyetheretherketone solution, so that the mass ratio of polyetheretherketone to the silane coupling agent-modified nano-silica is 2:1, stirring at room temperature for 2h, filtering, washing and drying to obtain the polyetheretherketone / nano-silica composite.

[0097] The silane coupling agent is γ-aminopropyltriethoxysilane.

[0098] Test Example 1:

[0099] The mechanical properties were tested in accordance with GB / T2951.11-2008 standard. The elongation at break was tested on a universal electronic tensile machine at a tensile speed of 500 mm / min. The average of three sets of data was taken. The results are shown in Table 1.

[0100] Table 1: Elongation at break test results

[0101] Elongation at break / % Example 1 36 Example 2 30 Example 3 22 Example 4 28 Example 5 16 Comparative Example 1 11 Comparative Example 2 32 Comparative Example 3 29 Comparative Example 4 28

[0102] Test Example 2

[0103] Its flame retardant performance is represented by UL94 vertical combustion, and the sample thickness is 1.6mm; its high temperature resistance is tested by thermal aging box, and the results are shown in Table 2.

[0104] Table 2: Flame retardant and high temperature resistance test results

[0105]

[0106]

[0107] As can be seen from Table 1, Example 1 has the best flexibility and the highest elongation at break. Example 2 does not modify the nano-silicon dioxide, resulting in a low polyetheretherketone loading rate, which causes a decrease in flexibility. Example 3 uses nano-silicon dioxide to replace the polyetheretherketone / nano-silicon dioxide composite, and the flexibility is further reduced. Example 4 uses polyetheretherketone to replace the polyetheretherketone / nano-silicon dioxide composite, and the flexibility is also lower than that of Example 1. Example 5 directly deletes the polyetheretherketone / nano-silicon dioxide composite, and the flexibility is further reduced.

[0108] From the perspective of flame retardancy and high temperature resistance, it can be seen from Table 2 that the nano-silicon dioxide exhibits good flame retardancy, while the flame retardancy of Example 4, Example 5, and Comparative Example 1, which do not contain nano-silicon dioxide, has decreased, indicating that the addition of nano-silicon dioxide can also play an excellent flame retardant role. Table 2 further shows that Examples 1-4 can pass the aging test at a high temperature of 300°C, while Examples 5 and Comparative Examples 1-3 cannot, indicating that the combination of polyimide, polyphenylene sulfide, and polybenzimidazole itself has excellent high temperature resistance, and the addition of the polyetheretherketone / nano-silicon dioxide composite further improves its high temperature resistance.

[0109] Since polyimide, polyphenylene sulfide, polybenzimidazole and polyetheretherketone composite modified by nano-silicon dioxide are included, these raw materials combine the characteristics of high strength and certain flexibility, therefore, the elongation at break of embodiment 1 is the highest. From the material properties, first, the polyimide molecular structure contains rigid aromatic rings and imide groups, which give it extremely high thermal stability and mechanical strength. However, this highly rigid structure also leads to limited flexibility of the material itself, and it is easy to have brittle fracture when subjected to stress. Secondly, polyphenylene sulfide is a typical liquid crystal polymer with a linear rigid molecular chain structure, and the aromatic ring in the molecule further enhances the rigidity of the material. Then, the molecular structure of polybenzimidazole contains benzimidazole rings, and this structure makes polybenzimidazole have extremely high heat resistance and mechanical strength, especially in high temperature environment, it can still maintain stability. However, polybenzimidazole has a large rigidity, and although it has excellent tensile strength, it also has the problem of insufficient flexibility, and it is easy to have brittle fracture under high stress. The common characteristics of these three materials are high rigidity, high strength, and good heat resistance, but relatively poor flexibility. The combination of polyimide, polyphenylene sulfide, and polybenzimidazole gives the material extremely strong high temperature resistance and can withstand high temperatures of 300°C, making it extremely suitable for metallurgical cable materials. However, when the material combination only contains polyimide, polyphenylene sulfide, and polybenzimidazole, it is easy to form a brittle material, especially in the case of stress concentration or uneven force, the material is more likely to break or break. Therefore, it is necessary to add flexible materials to make up for this defect.

[0110] As a semi-crystalline thermoplastic polymer, polyetheretherketone has certain flexibility and high elongation at break. Its molecular structure contains flexible ether bonds and ketone groups, which can introduce certain flexibility into the material structure and alleviate the brittleness problem caused by rigid polymers.

[0111] In composite materials, the role of polyetheretherketone is to provide flexibility and toughness, compensating for the rigidity brought by polyimide, polyphenylene sulfide and polybenzimidazole. When polyetheretherketone is missing, the overall flexibility of the material will be significantly reduced, and it is easy to cause brittle fracture under stretching, bending or impact.

[0112] After surface treatment, nano-silica can enhance the compatibility between polymers and improve the interfacial bonding force, thereby improving the toughness and strength of the composite material. In addition, nano-silica can form a uniform stress dispersion in the polymer matrix through good dispersibility, which helps to absorb externally applied energy and reduce the occurrence of brittle fracture. The lack of nano-silica will lead to poor compatibility between materials and easy formation of phase separation structure, which will further reduce the toughness and overall mechanical properties of the composite material.

[0113] If the flexibility of polyetheretherketone in the material is not reflected, it means that the material lacks sufficient energy absorption and deformation ability under high stress. The absence of nano-silicon dioxide not only reduces the interfacial compatibility of the composite material, but also loses the stress dispersion effect, which makes the material more prone to local stress concentration under the action of external force, thereby leading to fracture.

[0114] Finally, since polyetheretherketone has poor compatibility with other materials, nano-silicon dioxide also plays a role in improving the compatibility of polyetheretherketone with polyimide, polyphenylene sulfide, and polybenzimidazole. By treating the surface of nano-silicon dioxide, the loading rate of polyetheretherketone can be increased, the phase separation of polyetheretherketone in the blend can be prevented, and uniform dispersion can be promoted.

Claims

1. A high temperature resistant metallurgical vehicle-mounted flexible cable, characterized in that: It comprises three power lines, three control lines and an integrally formed high temperature resistant sheath, wherein the three power lines and the three control lines are located inside the integrally formed high temperature resistant sheath.

2. The high temperature resistant metallurgical vehicle-mounted flexible cable as claimed in claim 1, characterized in that: The material of the integrally formed high temperature resistant sheath is a flexible cable material for high temperature resistant metallurgy vehicles.

3. The high temperature resistant metallurgical vehicle-mounted flexible cable as claimed in claim 2, characterized in that: The high temperature resistant metallurgical vehicle-mounted flexible cable material is composed of the following raw materials by mass: 50-60 parts of polyimide, 1-3 parts of polyphenylene sulfide, 3-5 parts of polybenzimidazole, 10-12 parts of polyetheretherketone / nano-silicon dioxide composite, and 1-2 parts of anti-aging agent.

4. The high temperature resistant metallurgical vehicle-mounted flexible cable as claimed in claim 3, characterized in that: The anti-aging agent is at least one of styrene-butadiene copolymer and polyether polyol.

5. The high temperature resistant metallurgical vehicle-mounted flexible cable as claimed in claim 3, characterized in that: The preparation method of the polyetheretherketone / nano-silicon dioxide composite comprises the following steps: S1: mixing a silane coupling agent with ethanol, stirring at room temperature for 10-20 minutes to obtain an ethanol solution of the silane coupling agent, then mixing nano-silica with the ethanol solution of the silane coupling agent, stirring at room temperature for 1-2 hours, centrifuging, washing, and drying to obtain nano-silica modified with the silane coupling agent; S2: dissolving polyetheretherketone in N-methylpyrrolidone to obtain a 10-20wt% polyetheretherketone solution, adding the silane coupling agent-modified nano-silica obtained in step S1 to the above 10-20wt% polyetheretherketone solution, stirring at room temperature for 1-2h, filtering, washing and drying to obtain the polyetheretherketone / nano-silica composite.

6. The high temperature resistant metallurgical vehicle-mounted flexible cable as claimed in claim 5, characterized in that: The silane coupling agent is at least one of γ-aminopropyl triethoxysilane, γ-methacryloxypropyl trimethoxysilane, γ-glycidyloxypropyl trimethoxysilane and γ-aminopropyl trimethoxysilane.

7. The high temperature resistant metallurgical vehicle-mounted flexible cable as claimed in claim 5, characterized in that: The volume ratio of the silane coupling agent to ethanol is 1:(5-10).

8. The high temperature resistant metallurgical vehicle-mounted flexible cable as claimed in claim 5, characterized in that: The mass ratio of the nano-silicon dioxide to the ethanol solution of the silane coupling agent is 1:(10-20).

9. The high temperature resistant metallurgical vehicle-mounted flexible cable as claimed in claim 5, characterized in that: The mass ratio of the polyetheretherketone and the nano-silicon dioxide modified by the silane coupling agent is (1-2):

1.

10. A method for preparing a high temperature resistant metallurgical vehicle-mounted flexible cable according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: determining the structures of three power lines and three control lines, softening the high temperature resistant metallurgical vehicle-mounted flexible cable material, directly injection molding, and obtaining the high temperature resistant metallurgical vehicle-mounted flexible cable after cooling.

Citation Information

Patent Citations

  • High temperature resistant metallurgical vehicle-mounted flexible cable and its production process

    CN110675984B

  • Polyetheretherketone / polyimide / polyphenyl thioether ternary alloy and preparation method thereof

    CN103374199A

  • High-temperature-resistant and radiation-resistant sheath material for microwave oven wire harness and preparation method of high-temperature-resistant and radiation-resistant sheath material

    CN105968807A

  • High-temperature-resistant metallurgical vehicle-mounted flexible cable and production process thereof

    CN110675984A

  • High-temperature-resistant polyether-ether-ketone sealing check ring and preparation method thereof

    CN118725382A

Cited By

  • High-temperature-resistant and high-voltage-resistant cable for new energy automobile and preparation method thereof

    CN121812257A

  • A high-temperature and high-pressure resistant cable for new energy vehicles and a preparation method thereof

    CN121812257B